The role of self-reflection in facilitating cross-cultural adaptation as self-formation—a self-reflective diary approach. Issue 6 (2nd November 2018) - Xu, Xing
ABSTRACT: A passive adjustment paradigm of cross-cultural adaptation for international students has long been challenged by notions that endorse adaptation as a personal development process rife with positive experiences. A self-formation paradigm recently proposed by Marginson is one of the salient proposals. Insightful as it is, there is insufficient empirical testing of its validity. This paper aims to lend some empirical support to the notion of self-formation by analysing the author's personal experiences when navigating her overseas study trajectory as an international PhD student. A self-reflective diary approach was used to probe into two diary entries, which were experienced by the author as critical incidents. Each entry was analysed holistically referring to theoretical underpinnings in self-reflection and a self-formation paradigm. Analyses gave prominence to the primacy of multiplicity employed as the tool for self-formation, and they also communicated the involvement of another tool, hybridity, in this formation. This study corroborates that self-consciousness of self-change is embedded in the author's self-reflection, through which the author's cultural sensitivity is enhanced, aiding in smoothing over the author's cross-cultural adaptation.